Spin-Off as a Strategy to Accelerate Islamic Banking Growth in Indonesia: Assessing the Readiness of Sharia Business Units - Dja’akum, Cita Sary; Huda, Nur; Ryandono, Muhamad Nafik Hadi; Mujibatun, Siti; Mursyidi, Ach Fatayillah (Economica: Jurnal Ekonomi Islam, 2024)
Islamic banking in Indonesia has grown significantly in recent years, supported by legal mandates encouraging structural separation between conventional and Sharia banking. This study aims to assess the readiness of Sharia Business Units (UUS) to implement the 2023 spin-off policy. A qualitative research approach was employed, with data collected through documentation and literature review. The study examined 20 Sharia Business Units, including one unit from a State-Owned Enterprise (Bank Tabungan Negara), 13 units under Regionally-Owned Enterprises (BUMD), and six units affiliated with private banks. The findings show that 50% of the assessed Sharia Business Units are not prepared to separate from their parent banks, particularly in terms of asset size, capital adequacy, and overall institutional health. Most UUS lack sufficient capital readiness, infrastructure, and qualified human resources to operate independently. When viewed holistically—across financial, operational, and HR dimensions—the majority of UUS included in this study were not ready for the 2023 spin-off. These findings provide valuable insights for regulators and stakeholders in the Islamic banking industry, particularly in shaping future policies and support mechanisms for Sharia Business Units transitioning toward independence.